(untitled) (Revista Contexto & Saúde, 2025)
Dyslipidemia is characterized by a disorder in lipid metabolism and arises from external causes or predisposing genetic disorders. This observational, cross-sectional study aimed to analyze the correlation between the genetic polymorphisms RS10750097 and RS3741298 associated with the lipoprotein ApoA5-ZNF259 and the development of dyslipidemia. A sample of 200 Military Police officers from the state of Goiás was used, and genotyping of the polymorphisms was performed. Regarding the participating individuals, 93% were male and 7% were female. The polymorphisms observed in the groups with and without dyslipidemia showed a significant difference between the two groups for all variables analyzed (p<0.05) The present study found that the RS10750097 and RS3741298 polymorphisms did not increase the odds ratio of the dyslipidemia group actually having dyslipidemia (OR and 95% CI <1), which corroborates with previously described studies in different populations. Therefore, the RS10750097 and RS3741298 polymorphisms did not influence the development of dyslipidemia within the variables involved in this study and in this population, despite being part of the SNP spectrum of the APOA5 ZNF 259 region. Thus, the influence of each population’s epigenetics on the results is observed, and the need for similar research in other target groups is highlighted.